The Implementation of the Brain-based Learning Model in Elementary Schools Studied from a Literature Review - Oktaviani, Anna Maria; Gunardi, Ari; Supena, Asep (Universitas Sebelas Maret, 2023)
This research is to find out how the learning process of the